Lipomatous hypertrophy of the interatrial septum in ECG-gated multislice computed tomography of the heart - Czekajska-Chehab, Elżbieta (International Scientific Literature, Inc., 2012)
BACKGROUND: Lipomatous hypertrophy of the interatrial septum (LHIS) is a benign disorder characterized by fat accumulation in the interatrial septum (IAS). The purpose of the study was to analyze the incidental detection of LHIS in patients with various clinical conditions, referred to ECG-gated multislice computed tomography (ECG-MSCT) examinations of the heart. MATERIAL/METHODS: The ECG-MSCT examinations of 5786 patients (2839 women; 2947 men), were analyzed. The examinations were performed using 8-row (1015 patients) and 64-row (4771 patients) MSCT, in pre- and postcontrast scanning. We analyzed the shape of the IAS, density and maximal thickness of IAS, the thickness of the epicardial adipose tissue, and the degree of contact of IAS with the ascending aorta and superior vena cava. We also determined body mass index (BMI) in patients with LHIS. RESULTS: LHIS was detected in 56 (0.96%) patients, with an average age of 61.5±9.8 years. The mean BMI in the analyzed group was 30.1±4.86. During the end-diastolic phase the thickness of IAS was significantly higher (p<0.0001), and on average equaled 18.3mm. The mean optical density of the IAS was conspicuously higher (p<0.0001) in post-contrast phase than in pre-contrast phase. The thickness of the epicardial adipose tissue in the region of the left atrioventricular groove was on average 15 mm. In all cases the dumbbell shape of IAS was observed. CONCLUSIONS: The incidental frequency of LHIS occurrence in patients diagnosed with the ECG-MSCT examinations is about 1%. In most subjects it is linked with a higher BMI and increased thickness of the epicardial adipose tissue.